Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae) - Burckhardt, Daniel; Cho, Geonho; Lee, Seunghwan (Zootaxa, 2018)
Moriphila furva Burckhardt & Cho, gen. and sp. nov., is described from the mountain region in north eastern South Korea. Adults were collected on Morus australis which is a likely host. We provide morphological evidence that the new monotypic genus constitutes the probable sister group of the afrotropical Phytolyma whose species develop on Milicia and Morus (Moraceae). Differences between the two genera are detailed and the phylogenetic relationships to other members of Homotomidae: Macrohomotominae, to which the new genus belongs, are discussed. The host relationships of Psylloidea associated with Moraceae are reviewed. The latter constitutes the fifth most important host taxon of Psylloidea even though it is only a moderately large family of angiosperms in terms of constituent species. Moraceae have been colonised by psyllids at least five times independently. Following new combinations are proposed: Homotoma brevis (Li, 1993), comb. nov. and Homotoma microphyllae (Li & Yang, 1991), comb. nov. (both from Caenohomotoma Yang & Li, 1981).